化简逻辑函数:[img=330x77]17da59aad851bd0.png[/img],则Y=()。
举一反三
- 逻辑函数式Y=A+1,化简后结果是( );逻辑函数式Y=A[img=7x11]17e435c8c3e6f56.jpg[/img]1,化简后结果是( )。
- 逻辑函数[img=217x23]18036046eaff5aa.png[/img]化简结果正确的是 。 A: Y=A+D B: [img=63x21]18036046f2aea4f.png[/img] C: Y=AD D: Y=A+B
- 逻辑函数[img=147x24]17e0b255c637398.png[/img]化简结果正确的是。 A: Y=A B: Y=B C: Y=1 D: Y=A+B
- 逻辑函数[img=332x36]17e0b255a52a68f.png[/img]化简结果正确的是. 未知类型:{'options': ['', ' Y=A', ' Y=ABCD', ' [img=125x24]17e0b255b98f5bb.png[/img]'], 'type': 102}
- 逻辑函数[img=217x23]17e0b255d415633.png[/img]化简结果正确的是。 未知类型:{'options': ['Y=A+D', ' [img=63x21]17e0b255e186b74.png[/img]', ' Y=AD', ' Y=A+B'], 'type': 102}